2022
DOI: 10.3389/fmolb.2022.887686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel small non-coding RNAs and their modifications in bladder cancer using an updated small RNA-seq workflow

Abstract: Background: Bladder cancer (BLCA) is one of the most common cancer types worldwide. The disease is responsible for about 200,000 deaths annually, thus improved diagnostics and therapy is needed. A large body of evidence reveal that small RNAs of less than 40 nucleotides may act as tumor suppressors, oncogenes, and disease biomarkers, with a major focus on microRNAs. However, the role of other families of small RNAs is not yet deciphered. Recent results suggest that small RNAs and their modification status, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…They found that the expression of 5′-TRF-LySCtt in UBC tissue was positively correlated with the progression rate of UBC (multivariate Cox: HR = 2.368; p -value = 0.033) and negatively correlated with the prognosis of patients (multivariate Cox: HR = 2.151; p -value = 0.032) [ 21 ]. Another study found abundant tsRNAs in UBC which contained modifications that can be captured as a mismatch by TGIRT sequencing [ 22 ]. Lastly, TRMT6/61A-dependent base methylation of tsRNAs was stated to regμLate gene-silencing activity and the unfolded protein response in UBC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the expression of 5′-TRF-LySCtt in UBC tissue was positively correlated with the progression rate of UBC (multivariate Cox: HR = 2.368; p -value = 0.033) and negatively correlated with the prognosis of patients (multivariate Cox: HR = 2.151; p -value = 0.032) [ 21 ]. Another study found abundant tsRNAs in UBC which contained modifications that can be captured as a mismatch by TGIRT sequencing [ 22 ]. Lastly, TRMT6/61A-dependent base methylation of tsRNAs was stated to regμLate gene-silencing activity and the unfolded protein response in UBC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the rapid development of detection techniques, the great potential of small RNA modification as a biomarker of disease is being realized. For example, Su and workers used an improved RNA sequencing detection technique of Thermostable Group II Intron Reverse Transcriptase (TGIRT) and discovered the presence of m1A, m1G and N2, N2- dimethylguanosine (m 2 2 G) modifications on tsRNAs and rsRNAs in bladder cancer cells [ 180 ]. Yan and colleagues applied a highly efficient liquid chromatography-tandem mass spectrometry method and discovered that small RNA modifications in the liver cells of diabetic mice were significantly altered compared to control treatment, highlighting the correlation between small RNA modifications and diabetes [ 181 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Relatively little is known about the role of tRF in BC pathogenesis, though Su et al identified a specific tRF methylation pattern in BC cells that attenuated gene silencing of potential proto-oncogenes. tRFs with specific methylation patterns may thus be drivers of oncogenesis in BC [15][16][17].…”
Section: Introductionmentioning
confidence: 99%